Comparative evaluation of root canal morphology of mandibular premolars using clearing and cone beam computed tomography - Abbasali Khademi; Mojdeh Mehdizadeh; Maryam Sanei; Hamidreza Sadeqnejad; Saber Khazaei (Wolters Kluwer Medknow Publications, 2017)
Background: Different techniques are used to evaluate the anatomy of root canal system. The present study was aimed to evaluate the root canal morphology of mandibular premolars using clearing and cone beam computed tomography (CBCT) techniques. Materials and Methods: A total of 182 mandibular first and second premolars were evaluated in vitro using 100 μm CBCT cross sections. The root canal morphology of the teeth was determined based on Vertucci classification in relation to the prevalence of C-shaped canals, lateral canals, and furcation location. Having removed the pulp tissue with NaOCl solution and staining the root canals with India ink, the samples were decalcified with 5% nitric acid and dehydrated with isopropyl alcohol. Finally, the samples were cleared with methyl salicylate. Data were analyzed by SPSS 16 software using McNamara, t-test, and Kappa coefficient. Results: After Type I, the most frequent morphologies in both first and second premolars were Type V followed by Type IV. The prevalence rates of C-shaped morphology in first premolars using clearing and CBCT were 4.4% and 6.6%, respectively. However, no C-shaped morphology was found in second premolars. The maximum and minimum levels of agreement between the two techniques were observed in Type IV and Type V root canal morphologies, respectively. Extra root canals were identified in 25% and 13% of the first and second premolars, respectively. Conclusion: CBCT showed a higher accuracy in determining C-shaped root canal morphology than the clearing technique. It also showed the least accuracy in diagnosing lateral root canals.